Facilitating public participation in urban planning : a case study of Abuja, Nigeria - Yusuf Sani Stores, 1984-; Norsiah Abdul Aziz; Fakulti Alam Bina (2014)
Thesis (Sarjana Sains (Perancangan Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2014